COOPERATION INITIATIVES BETWEEN THE DIRECTORATE GENERAL OF IMMIGRATION AND THE AUSTRALIAN GOVERNMENT ON AIRPORTS IN INDONESIA - Marsiyah Daliman; Ridwan Arifin (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2020)
This study is to examine the nature of collaboration between the Department of Home Affairs Australia (DHA) and the Directorate General of Immigration Indonesia (DGI) to protect their borders and intercept unauthorized arrivals, and to identify current challenges of postings of Airline Liaison Officers (ALOs) at airports in Indonesia. This study employs the qualitative research method methodology using the document analysis and observation at Jakarta and Bali airports by collecting sources of data from public organizational reports, official documents, books, online publications, or journal articles. The data is analyzed by using the five indicators by Oâ€™Leary & Vij: power, communication, perceived legitimacy, trust, and information exchange. The study shows the collaboration between DHA and DGI in posting of ALOs at airports in Indonesia has been running for more than a decade as the extraterritorial immigration control despite legal challenges, sovereignty, non-refoulment principles, human rights violations, and authority overlap. This paper recommends both countries to ratify new arrangements about posting of ALOs subject to the national sovereignty, data sharing, use of technology, Indonesian legislations, and involvement in operation protocols. Further study aboutÂ extraterritorial immigration control by postings of ALOs in Indonesia can be discussed from the perspectives of national sovereignty, border integrity, and intelligence service.Keywords: DHA, extraterritorial immigration control, ALOs, unauthorised arrivals, perceived legitimacy